CULTURE AND WOMEN SARA ABOOBAKER AND B.T NOVELS - Sunil Kumar Pandey (International Journal of Multidisciplinary Research and Studies, 2021)
Some less powerful parties could be forced to accept a representation if it is imposed by a more strong group. In this respect, it is applicable to the research of underrepresented groups, such as women and underprivileged populations. It is not uncommon for representations to give rise to a shared sense of identity, which, once formed, continues to exist. However, the process that led to its creation will not go away or become less noticeable. For instance, some of the marginalized Indian communities and tribes were branded as criminal tribes by the British, and they suffered the stigma even after they were de-notified by the Indian government after independence. Furthermore, women are portrayed as the inferior gender in all of the world's cultures. Stuart Hall is a proponent of establishing a connection between literary theory's comprehension of the construction of meaning and textual interpretation and social theory's delineation of competing forces present in the social field. Any understanding of a piece of literature needs to take into account not just the hegemonic work that the text accomplishes, but also the social factors that contribute to the production of the text.